Global climate crisis and regional contexts. A study on ecosystem services related to Sardinia, Italy - Isola, Federica; Kobak, Bilge; Leccis, Francesca; Leone, Federica; Zoppi, Corrado (TeMA - Journal of Land Use, Mobility and Environment, 2025)
A methodology that aims to implement climate neutrality through spatial planning is defined and applied. The measure of carbon sequestration (CS) is taken as a reference to estimate the status and evolutionary dynamics of this phenomenon, analyzed as associated with the supply of certain types of ecosystem services (ESs), in relation to the reference spatial context. The study is developed as follows. The multifunctionality of the supply of ESs can be considered as an analytical reference for the definition of a system of measures oriented to the improvement of CS capacity and, therefore, of the contribution of local spatial planning policies to the effective pursuit of global climate neutrality. Based on previous studies and in-depth analyses of environmental, landscape, and socio-cultural contexts, the provision of ESs related to the regional territory of Sardinia is characterized in this study and the correlations between the spatial taxonomies of CS capacity and ESs supply with regard to the regional context are detected and analyzed, in order to assess how the characteristics and specificities of the multifunctional ESs supply can be effectively used in order to maximize CS capacity, and, thus, the contribution of the Sardinia region to the improvement of global climate neutrality.